Analysis of the January effect phenomenon in companies included in the LQ45 Stock Index on the Indonesia Stock Exchange for the 2018-2021 period - Evianti, Ebi; Ratnaningrum, Natalia; Afriany, Arista Natia (Proceeding International Conference on Accounting and Finance, 2024)
This study aims to determine whether there is a January effect phenomenon as seen from the difference in actual return and abnormal return of shares of companies included in the LQ45 index on the Indonesia Stock Exchange for the 2018-2021 period. The sample in this study were 28 companies obtained through purposive sampling method. This research data analysis uses the Paired Sample t-test and Wilcoxon Sign Rank Test with the Kolmogorov Smirnov normality test. Based on the analysis conducted, it is stated that there is not enough evidence where there is a difference in actual return and abnormal return of stocks in January with eleven other months, even from these eleven months only three months there is a significant difference in actual return where January is greater than February, March, and September. As for the abnormal return test results, January is greater than February and March.